Marked enhancement of the immune response to BioThrax® (Anthrax Vaccine Adsorbed) by the TLR9 agonist CPG 7909 in healthy volunteers - Rynkiewicz, Dianna; Rathkopf, Melinda; Sim, Iain; Waytes, A. Thomas; Hopkins, Robert J.; Giri, Lallan; DeMuria, Deborah; Ransom, Janet; Quinn, James; Nabors, Gary S.; Nielsen, Carl J. (Vaccine, 2011)
Immunization with BioThrax® (Anthrax Vaccine Adsorbed) is a safe and effective means of preventing anthrax. Animal studies have demonstrated that the addition of CpG DNA adjuvants to BioThrax can markedly increase the immunogenicity of the vaccine, increasing both serum anti-protective antigen (PA) antibody and anthrax toxin-neutralizing antibody (TNA) concentrations. The immune response to CpG-adjuvanted BioThrax in animals was not only stronger, but was also more rapid and led to higher levels of protection in spore challenge models. The B-class CpG DNA adjuvant CPG 7909, a 24-base synthetic, single-strand oligodeoxynucleotide, was evaluated for its safety profile and adjuvant properties in a Phase 1 clinical trial. A double-blind study was performed in which 69 healthy subjects, age 18–45 years, were randomized to receive three doses of either: (1) BioThrax alone, (2) 1mg of CPG 7909 alone or (3) BioThrax plus 1mg of CPG 7909, all given intramuscularly on study days 0, 14 and 28. Subjects were monitored for IgG to PA by ELISA and for TNA titers through study day 56 and for safety through month 6. CPG 7909 increased the antibody response by 6–8-fold at peak, and accelerated the response by 3 weeks compared to the response seen in subjects vaccinated with BioThrax alone. No serious adverse events related to study agents were reported, and the combination was considered to be reasonably well tolerated. The marked acceleration and enhancement of the immune response seen by combining BioThrax and CPG 7909 offers the potential to shorten the course of immunization and reduce the time to protection, and may be particularly useful in the setting of post-exposure prophylaxis.